Upper gastrointestinal active bleeding ulcers: review of literature on the results of endoscopic techniques and our experience with Hemospray. (November 2014) - Masci, Enzo; Arena, Monica; Morandi, Elisabetta; Viaggi, Paolo; Mangiavillano, Benedetto
Abstract Introduction and objectives. Acute gastrointestinal (GI) bleeding can lead from mild to immediately life-threatening clinical conditions. Upper GI bleeding (UGIB) is associated with a mortality of 6–10%. Spurting and oozing bleeding are associated with major risk of failure. Hemospray™ (TC-325), a new hemostatic powder, may be useful in these cases. Aim of this study is to review the efficacy of traditional endoscopic treatment in Forrest 1a-1b ulcers and to investigate the usefulness of Hemospray in these patients. Patients and methods. A MEDLINE search was performed and articles that evaluated hemostatic efficacy and rebleeding rate with traditional endoscopic techniques related to Forrest classification were reviewed. Patients with Forrest 1a–1b ulcers were treated with Hemospray, either as monotherapy or in association with other endoscopic techniques. Primary outcome was immediate hemostasis, secondary outcomes were recurrent bleeding and adverse events related to Hemospray use. Results. Analysis of literature showed that mean initial hemostasis success rate in Forrest 1a–1b ulcers was of 92.8%, and mean rebleeding rate was of 13.3%. We enrolled 13 patients treated with Hemospray. Initial hemostasis was achieved in 100% and we reported three cases of rebleeding. No adverse events occurred. Conclusion. Forrest 1a–1b bleeding ulcer is very difficult to treat. Hemospray appears to be an effective hemostatic therapy for these ulcers. However, additional prospective studies are needed to validate these findings.